The essential role of genetic resources in narrow-leafed lupin improvement - Berger, J.; Clements, J.; Nelson, M.; Kamphuis, L.; Singh, Karambir; Buirchell, B. (CSIRO Publishing, 2013)
The narrow-leafed lupin (Lupinus angustifolius L.) is a legume with much to offer to agriculture and human wellbeing through its adaptation to nitrogen- and phosphorus-deficient, acid, sandy soils, and production of nutritious, very low glycemic index grain with manifold health benefits. However, the industry has exploited only a small fraction of the genetic and adaptive diversity of the species, reflecting a short and fragmented domestication history. Given declining global production, unlocking the potential residing in untapped sources of genetic diversity to maximise yield and value is critical for the future of the crop. To this end, a wide range of genetic resources is under evaluation. The Australian Lupin Collection comprises almost 4600 diverse, mostly wild accessions, many of which have been genotyped using DArT (Diversity Array Technology) markers, and collection sites characterised to facilitate ecophysiology of contrasting material. Additional exotic genetic resources include recombinant inbred line and mutant populations, as well as inter-specific crosses. These resources are being used to investigate specific adaptation and genetic and molecular control of key traits, all of which will be expedited by current efforts to provide a reference genome sequence for L. angustifolius. Genetic base broadening is the current breeding focus, combining distantly related wild and domestic material with elite cultivars in double-backcrosses or topcrosses, with dramatic effects on yield. In future this will be complemented by marker-based, targeted trait introgression to improve narrow-leafed lupin adaptation, quality/value, and fit into the farming system. © CSIRO 2013.